Numerical investigation of composite materials with short fibers made of carbon nanotubes [electronic resource] - 491370 Iman Eslami Afrooz; Fakulti Kejuruteraan Mekanikal (2010)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010